(untitled) (Jurnal Destinasi Pariwisata, 2025)
This study aims to analyze the existing conditions of the development of Jasan Waterfall tourist attractions based on the theory of Tourism Area Life Cycle (TALC), as well as analyze the role of stakeholders in its development. The research method used is a qualitative descriptive method with data collection techniques through observation, interviews, documentation, and literature studies. The results of the study show that Jasan Waterfall is at the involvement stage. The main characteristics of this stage are shown by the increasing number of visits, community involvement in management, and the emergence of promotional initiatives and basic facilities. However, external support and institutional development are still limited. The role of stakeholders in development is quite significant, especially from the village government, land owners, and Jasa Traditional Villages. The village government plays a role in policy formulation and infrastructure development, while the community is involved in operational activities and environmental conservation. Private sector involvement is still minimal, and coordination between stakeholders is not optimal. This study concludes that the success of the development of Jasan Waterfall tourist attractions is highly dependent on strengthening cross-sector collaboration and continuous support from all stakeholders involved. land owners contribute to the management and provision of initial facilities, Jasan Traditional Village as a liaison for cooperative communication between the Village Government and land owners. Meanwhile, academics and pokdarwis are still not much involved